Sales impact of servicescape's emotional and rational stimuli: A survey study - Andrea Morone; Francesco Nemore; Dario Antonio Schirone (Economics and Econometrics Research Institute (EERI), 2018)
Environmental psychologists suggest that people feelings and emotions determine what they do and how they do it. According to the stimulus organism respons model (SOR), the environment creates a behavioral/emotional response in individuals that, in turn, induces approach or avoidance behaviors. We conducted survey in six stores, settled in six different Italian cities, of a Swedish-founded Dutch-based multinational group, that designs and sells ready-to-assemble furniture, kitchen appliances and home accessories. Firstly, we apply the SOR model to evaluate loyalty program participation impact on consumers receipts. Subsequently, we provide empirical evidence about the effects of an emotional-sensorial stimulus (i.e. the presence of the restaurant inside the store). Through both a non-parametric and parametric testing, we found that environmental stimuli have a positive effect in terms of sales.
Keywords: L83; 330; Servicescape; sensorial stimuli; functionality; loyalty; restaurant